PELAKSANAAN PUTUSAN HAKIM YANG TELAH BERKEKUATAN HUKUM TETAP ATAS PENGEMBALIAN BARANG BUKTI DI KEJAKSAAN NEGERI INDRAGIRI HULU - Setio, Heri Anjar; Indra, Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The AGO is not only in charge of prosecution, but also as executor of the judge's decision which has obtained permanent legal force, as regulated in Article 270 of the Criminal Procedure Code which appoints the prosecutor as the executor of the court decision. Therefore the Public Prosecutor's Office Indragiri Hulu in addition to the prosecution of criminal acts, also focused on the evidence that has been picked on the content of court decisions. Which is known in terms of execution of judicial decisions by judges about the evidence is so under-emphasized because in the case of the trial, the defendant in the case of the criminal act is focused. Judging from its authority, the prosecutor's office has the right in returning the evidence which has been listed by the judge in the execution of the court decision whether it belongs to the defendant or the victim, judging from the storage place of the evidenced so much, the writer is interested to examine the execution of the judge's verdict which has the permanent legal force for the return of evidence at the Indragiri Hulu State Prosecutor Office.The researcher wants to study and answer the problem of how the execution of the judge's decision which has the permanent legal force over the return of the evidence? as well as the barriers that occur in the implementation of the return of evidence that has obtained legal force remains? and also how the efforts undertaken in overcoming the barrier of return of evidence that has obtained legal force remains?The method that writer use is by method of sociological approach with collecting data as follows: literature study, document study, and interview.The results of the study and discussion can be concluded that the judge made a letter of passage of the verdict, the decisions came out 1 week after the verdict was read by the judge. The petition of the verdict is then granted to the prosecutor for the prosecutor to prepare the minutes of the judge's determination (BA-6) and make the report of the evidence-taking event (BA-20), then (BA-6) and (BA-20) awarded to the defendant or party which is mentioned in the contents of the decisions made by the judge, because the minutes of the proceedings constitute notification of the collection of evidence as stated in the contents of the decision in the Prosecution or RUPBASAN. Constraints in the implementation of the return of evidence by the prosecutor that the lack of clarity of the address to the owner of the evidence, the vehicle is still a credit, and the period of return of evidence has not been set in concrete causing the storage space of evidence becomes full, Suggestion case author who has received the decision of Inkracht Prosecutor the executor of the judge's verdict shall promptly return the evidence to the person mentioned in the content of the decision or those who are entitled in accordance with the laws governing it. As well as the addition and renewal of infrastructure to minimize the accumulation of evidence at the AGO and RUPBASAN.Keywords: Procurator - Goods Proven - Judge's Decision